BUDGET PAYMENTS AND ECONOMIC GROWTH (Globalization and Business, 2023)
The study of the relationship between fiscal policy and economic growth has received a great deal of attention in both developed and developing countries. An effective fiscal policy contributes to the economic growth and stabilization of the country. Determining the optimal level of budget expenditures is an important prerequisite for forming an effective budget. Separate science papers suggest that fiscal policy may affect economic growth in different degrees and forms, although the results vary from country to country. The article presents the optimal size of government for Georgia calculated as a result of the research.